Penggunaan Factory Method Design Pattern Pada Framework Flask di Dalam Aplikasi Dashboard - Sumbaluwu, Devin William; Somya, Ramos (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
Problems related to the use of an object of Flask for various environments are often caused by application designs that are less effective and efficient. An object of Flask is used to run a Flask application based on the states or application environments. Each state or environment has different configuration requirements. The factory method design pattern solves the design problem by separating functions that return an object of Flask based on another object of the configuration class. The implementation of the factory method design pattern will be realized in a dashboard website. It will be used on the backend so that there will be a unit test code to prove the app can be run in a different state or environment